2014
DOI: 10.1017/s0016756814000405
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb zircon geochronology of volcanic deposits from the Permian basin of the Orobic Alps (Southern Alps, Lombardy): chronostratigraphic and geological implications

Abstract: U–Pb zircon ages from volcanic rocks of Early Permian age (Southern Alps, Lombardy), associated with fault-controlled transtensional continental basins, were determined with the laser ablation (LA)-ICP-MS technique. Four samples were collected at the base and at the top of the up to 1000 m thick volcaniclastic unit of the Cabianca Volcanite. This unit pre-dates the development of a sedimentary succession that still contains, at different stratigraphic levels, volcanic intercalations. Age results from a tuff in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…288 Ma (Cadel et al, 1987), ca. 280 Ma (Philippe et al, 1987), 280 ± 2.5 Ma and 270 ± 2 Ma (Berra et al, 2014).…”
Section: Stratigraphic Inferencesmentioning
confidence: 95%
See 2 more Smart Citations
“…288 Ma (Cadel et al, 1987), ca. 280 Ma (Philippe et al, 1987), 280 ± 2.5 Ma and 270 ± 2 Ma (Berra et al, 2014).…”
Section: Stratigraphic Inferencesmentioning
confidence: 95%
“…While the ages of Cadel (1986) and Cadel et al (1987) are affected by hydrothermal alteration so they could show older values (Cadel et al, 1996), the youngest age indicated by Berra et al (2014) could be due to "a complex mixing of antecrystic and autocrystic zircon populations in the analysed samples" (Berra et al, 2014). Thus, since both the end-members' ages (i.e the early Artinskian ones -ca.…”
Section: Stratigraphic Inferencesmentioning
confidence: 97%
See 1 more Smart Citation
“…The Pizzo del Diavolo formation is dated late Early Permian (Cisuralian) to early Middle Permian (Guadalupian) by radiometric ages on the underlying Vulcanite del Cabianca (Berra et al . ), while the tetrapod ichnoassociation, recently revised by Marchetti et al . (, ) and Marchetti (), is most probably Late Cisuralian (Kungurian) in age.…”
Section: Methodsmentioning
confidence: 99%
“…), while radiometric dating (Berra et al . ) indicates a late Kungurian or Guadalupian age. Therefore, the assemblage covers a gap in the Permian footprint record.…”
mentioning
confidence: 99%